An Optimality-Theoretic Analysis of the Acquisition of English Sentence Stress Based on Acoustic Data - Wen Ji; Yun Liu (Complexity)
The present study adopts both empirical and theoretical methods for the analysis of the acquisition of English sentence stress based on Optimality Theory, aiming to overcome mispronunciation of English sentence stress. Optimality Theory has a dramatic impact on most areas in linguistics besides phonology. The acoustic software Praat is chosen to collect and label data as the basis of the empirical method. Then, through analyzing the four major principles of distribution of sentence stress (content words stressed principle, rightmost words stressed principle, leftmost words stressed principle, and new information priority principle) and based on the analysis of Optimality Theory, the software Praat, and SPSS, the researcher can present the following findings: firstly, the constraint hierarchical ranking of nonnative speakers is DEP-IO >> NEW-IP >> ALIGN-IP-LEFT >> ALIGN-IP-RIGHT. Secondly, the native speakers also undergo the demotion of constraint hierarchical ranking: NEW-IP >> DEP-IO >> ALIGN-IP-RIGHT >> ALIGN-IP-LEFT. Thirdly, the constraint in each demotion of constraint hierarchical ranking during different stages is as follows: NEW-IP constraint moves from the undominated position to the dominated position in the hierarchy; ALIGN-IP-RIGHT and ALIGN-IP-LEFT constraints move from the dominated position to the lower position in the hierarchy. Through the specific analysis, the researcher draws a conclusion that the varied reasons affect the nonnative speakers to master the distribution of sentence stress due to their incorrect position in the demotion of constraint hierarchical ranking.